High-throughput sequencing revealed novel Dehalococcoidia in dechlorinating microbial enrichments from PCB-contaminated marine sediments. Issue 11 (11th October 2017) - Matturro, Bruna; Frascadore, Emanuela; Rossetti, Simona
Abstract: In this study, six PCE-to-ethene dechlorinating cultures, fed with a fermentable substrate (lactate) or hydrogen as electron donor, were obtained from PCB and PCE dechlorinating microcosms constructed with PCB-contaminated marine sediments. A novel Chloroflexi member (OTU-DIS1) affiliated to Dehalococcoidales Incertae Sedis, only distantly related to known dechlorinating bacteria, dominated the enrichment cultures (up to 86% of total OTUs). Sulfate-, thiosulfate- and sulfur-reducing bacteria affiliated to genera Desulfobacter, Dethiosulfatibacter and Desulfuromusa were also found to lesser extent. Remarkably, tceA, vcrA and the bifunctional PCE/PCB dehalogenase genes pcbA1, pcbA4 and pcbA5 were found in all dechlorinating microbial enrichments indicating the coexistence of different Dehalococcoides mccartyi strains. The reductive dechlorination rate in each culture remained unvaried over long-term operation (≈ 30 months) and ranged between 0.85 and 0.97 mmol Cl −1 released L −1 d −1 in the lactate-fed microbial enrichments and between 0.66 and 0.85 mmol Cl −1 released L −1 d −1 in the H2 -fed microbial enrichments. Overall, this study highlights the presence of yet unexplored biodiversity in PCBs contaminated marine sediments and indicates these environments as promising sources of novel organohalide-respiring bacteria. Abstract : Novel Dehalococcoidia found in dechlorinating microbial enrichments from PCB-contaminated marine sediments.